Characterization of calcium oxalates generated as biominerals in cacti - Monje, Paula V. (2002)
The chemical composition and morphology of solid material isolated from various Cactaceae species have been analyzed. All of the tested specimens deposited high-purity calcium oxalate crystals in their succulent modified stems. These deposits occurred most frequently as round-shaped druses that sometimes coexist with abundant crystal sand in the tissue. The biominerals were identified either as CaC 2 O 4 .2H 2 O (weddellite) or as CaC 2 O 4 .H 2 O (whewellite). Seven different species from the Opuntioideae subfamily showed the presence of whewellite, and an equal number of species from the Cereoideae subfamily showed the deposition of weddellite. The chemical nature of these deposits was assessed by infrared spectroscopy. The crystal morphology of the crystals was visualized by both conventional light and scanning electron microscopy. Weddellite druses were made up of tetragonal crystallites, whereas those from whewellite were most often recognized by their acute points and general star-like shape. These studies clearly demonstrated that members from the main traditional subfamilies of the Cactaceae family could synthesize different chemical forms of calcium oxalate, suggesting a definite but different genetic control. The direct relationship established between a given Cactaceae species and a definite calcium oxalate biomineral seems to be a useful tool for plant identification and chemotaxonomy.